2015
DOI: 10.1097/bsd.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

MRI Morphology of Surgically Treated Lumbar Canal Stenosis

Abstract: LCS seems to produce predictable patterns on T2 axial MRI. The triangular configuration correlates most frequently with surgical LCS. Further studies are needed in normal individuals, in prospective patients, and to determine the outcome of treatment based on MRI morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…43 None of the quantitative parameters measured on X-rays, computed tomography scans, or magnetic resonance imaging (MRI) correlates well with the severity of clinical symptoms in lumbar canal stenosis. 44 The LSS Outcome Study Working Group with 41 musculoskeletal and neuroradiologists recently published the results of their Delphi survey, 45 where they concluded that none of the quantitative parameters was uniformly acceptable for the diagnosis of lumbar canal stenosis and only some of the quantitative parameters were partially accepted. Lumbar canal stenosis seems to produce predictable patterns on T2 axial MRI.…”
Section: Surgical Treatment Of Lumbar Spinal Stenosismentioning
confidence: 99%
See 2 more Smart Citations
“…43 None of the quantitative parameters measured on X-rays, computed tomography scans, or magnetic resonance imaging (MRI) correlates well with the severity of clinical symptoms in lumbar canal stenosis. 44 The LSS Outcome Study Working Group with 41 musculoskeletal and neuroradiologists recently published the results of their Delphi survey, 45 where they concluded that none of the quantitative parameters was uniformly acceptable for the diagnosis of lumbar canal stenosis and only some of the quantitative parameters were partially accepted. Lumbar canal stenosis seems to produce predictable patterns on T2 axial MRI.…”
Section: Surgical Treatment Of Lumbar Spinal Stenosismentioning
confidence: 99%
“…Further studies are needed in prospective patients and in normal individuals to determine the outcome of treatment based on MRI morphology. 44 Substantial evidence in the literature indicates that at > 65 years of age, degenerative changes in the intervertebral disk, facet joints, and osteophytes can contribute to the development of radiologic or pathologic evidence of spinal canal narrowing in 80 to 100% of the population. [46][47][48] However, the clinical incidence of spinal stenosis in the United States has only been calculated as between 3% and 14%.…”
Section: Surgical Treatment Of Lumbar Spinal Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…4,10,15 Neuroimaging techniques have significantly expanded the diagnostic capabilities for early verification of degenerative spinal diseases, which in turn, has led to an increase in the number of surgical interventions for spinal stenosis. 16,17 However, certain difficulties still remain in diagnosing the disease and choosing objective indications for surgery. The criteria for comparison of clinical neurological symptoms and pathomorphological compression factors of combined tandem stenosis, which are visualized by radiographic techniques, are not fully presented.…”
Section: Introductionmentioning
confidence: 99%
“…клиническая комплексная оценка неврологической симптоматики, непосредственно зависящей от степени сужения позвоночного канала и межпозвонкового отверстия при сочетанных тандем-стенозах, определяет выбор оперативного вмешательства [4,10,15]. нейровизуализационные методы исследования значительно расширили диагностические возможности ранней верификации дегенеративных заболеваний позвоночника, что определило тенденцию к увеличению числа хирургических вмешательств по поводу стенозов позвоночного канала [16,17].…”
unclassified